Physical activity among nursing students measured with the International Physical Activity Questionnaire and their BMI - Waksmańska, Wioletta; Bobiński, Rafał; Wiczkowski, Andrzej; Pielesz, Anna (Polish Journal of Public Health, 2018)
Introduction. Excessive body weight associated with modern lifestyle may result from overeating due to stress, sleep deprivation leading to increased appetite, insufficient physical activity and changes in dietary habits.Aim. The aim of the study was to assess the amount of physical activity among female working undergraduate and graduate nursing students and the influence of this activity on their BMI values.Material and methods. Undergraduate extramural students consisted 58 students (group I) and graduate full-time and extramural students – 45 (group II). The research involved calculating each student’s BMI value which was categorized in accordance with the World Health Organization (WHO) recommendations. The measurement of physical activity was conducted on the basis of the  International Physical Activity Questionnaire (IPAQ).Results. Group I students more frequently presented abnormal body weight, with 47% being overweight. In group II, 24.5% of the respondents were overweight and 4.5% were underweight. We revealed a significant correlation between the time spent on intensive physical activity, both at work and during recreation at home, and the BMI value decreases as the time devoted to intensive physical activity increases.Conclusions. The education system is recommended to be redesigned in such a way as to enable students to spend more time on physical activity.